2011
DOI: 10.1007/s10517-011-1195-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucocorticoid Receptor Blockade on Analgesic Effect of Corticotropin-Releasing Factor

Abstract: The role of glucocorticoid receptors in the analgesic effect of corticotropin-releasing factor in rats was studied after glucocorticoid receptor blockade with antagonist RU 38486. Glucocorticoid hormones can potentiate the analgesic effect of corticotropin-releasing factor or modulate the mechanisms of this effect, which depends on the type of painful stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
0
2
Order By: Relevance
“…At present, there is only one study that actually showed an endogenous opioid peptide release from neurons within the brain of animals with inflammatory pain [ 33 ]. Our findings are in contrast to the study by Yarushkina et al [ 34 ] in which i.c.v. applied CRF-induced antinociceptive effects apparently by a non-opioid mechanism via the activation of the hypothalamic–pituitary–adrenal stress axis [ 34 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…At present, there is only one study that actually showed an endogenous opioid peptide release from neurons within the brain of animals with inflammatory pain [ 33 ]. Our findings are in contrast to the study by Yarushkina et al [ 34 ] in which i.c.v. applied CRF-induced antinociceptive effects apparently by a non-opioid mechanism via the activation of the hypothalamic–pituitary–adrenal stress axis [ 34 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are in contrast to the study by Yarushkina et al [ 34 ] in which i.c.v. applied CRF-induced antinociceptive effects apparently by a non-opioid mechanism via the activation of the hypothalamic–pituitary–adrenal stress axis [ 34 ]. I.c.v.…”
Section: Discussioncontrasting
confidence: 99%